Talent Leadership a proven method for identifying and developing high-potential employees - Mattone, John. (New York American Management Association, 2013)
Talent Leadership unlocks the secret of building a world-class leadership identification and development program by using assessment and calibration as foundational tools. Unlike most leadership development efforts that look at "lagging indicators", such as cost per hire or turnover, this book identitfies far more important metrics that actually predict operating results: the "leading indicators" of capability, commitment, and alignment with organizational goals. Paked with research findings, best practices, case studies, proprietary assessments, and more, the book explains the key components of exceptional leadership development practices employed by great organisations, including how to: Employ assessments to benchmark current and future excutive talent, use the resulting data to identify leaders with potential based on their capabilities, commitment, and alignment with organisational goals, leverage your analysis to target training and coaching where they will have the greatest impact on individual performance and overall operating success. Talent Leadership helps you push past the myopic practices of hiring and promoting technically proficient people who lack the motivation and and vision to successfully lead.
Includes bibliographical references (p. 267-269) and
Keywords: Personnel management